Population Structure of Bamboo Shell (Solen lamarckii) in the Intertidal Zone of Sri Tanjung Village, Rupat District, Bengkalis Regency - Nanang Tri Prastyo; Syafruddin Nasution; Feli Feliatra (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Research on the population structure of bamboo shells (Solen lamarckii) in the intertidal zone of Sri Tanjung Village, Rupat District, Bengkalis Regency was carried out in October 2021-March 2022. This study aimed to determine the population structure of bamboo shells and the relationship between the size of bamboo shells and the depth of bamboo shells in the sediment. The intertidal zone is divided into 5 subzones. Each subzone is placed in 3 plots measuring 1 x 1 m2 along the transect line as a replication by drawing a straight line from the boundary of the highest tide area to the lowest low tide area. The results showed that the average population density of bamboo shells was 1.20 ind/m2 or 12,000 ind/ha with the lowest density located in the highest tide area and the highest density located in the lowest low tide area. The distribution pattern of bamboo shells is uniform. The size of the most common bamboo shells found is 5.14-5.70 cm. The relationship between the size of the bamboo shells and the depth of the bamboo shells in the sediment is very weak